Upper secondary school students' understanding of adiabatic compression - KALIOPI MELI; DIMITRIS KOLIOPOULOS; KOSTAS LAVIDAS; GEORGE PAPALEXIOU (Metaichmio Publications, 2016)
The present study refers to second year (16-17 years old) upper secondary school students' conceptions on elementary thermodynamics and especially the First Law of Thermodynamics (FLT). This paper focuses on students' explanations of a real situation representing an adiabatic compression and their forms of reasoning in providing explanations. We used descriptive statistics and hierarchical cluster analysis in order to process students' answers. The main results were that (a) the vast majority of the responses consisted of alternative frameworks, namely FLT is highly disregarded among the students, (b) the students provided confused explanations that entangle diverse physics models and/or referred to the phenomenology of the situation and (c) linear causal reasoning was the prevailing way for providing explanations, although it was inadequate for this physics level.